The Relationship Mean Arterial Pressure and Sleep Quality with The Incident of Tension Type Headache - Susanto, Syarafina Ayu Putri; Setiawan, Iwan; Sulistyani, S; Herawati, Erna (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Background: Headache is one of the most prevalent neurological illnesses seen in emergency departments. Tension Type Headache (TTH) is the most prevalent type of headache, affecting up to 70% of people aged 18 to 65 globally. Risk factor of TTH often discussed include poor sleep quality and vascular control. According to studies, poor sleep quality increases the frequency and intensity of headaches, including TTH. Furthermore, vascular control, particularly Mean Arterial Pressure (MAP), is thought to be associated with TTH. Previous research suggests that high blood pressure may diminish the occurrence of TTH via a mechanism known as hypertension-induced hypoalgesia, while evidence on the link between MAP and TTH are sparse. Purpose: This study aims to evaluate the relationship between mean arterial pressure, sleep quality, and the occurrence of tension-type headache. Methodology: The study was conducted in Surakarta Boarding High School using a cross-sectional design. The sample approach used was simple random sampling. The data was examined using univariate and bivariate statistics. The chi-square and Fisher's exact tests were used to do bivariate analysis. Results: The bivariate analysis revealed that the p-value for the association between mean arterial pressure and the incidence of TTH is 0.694, and the p-value for the relationship between sleep quality and the occurrence of TTH is 0.992. Applications: The study's findings show that Mean Arterial Pressure and sleep quality had no relationship with the incidence of Tension Type Headache. Thus, further research is needed to explore this risk factor more deeply, enabling clinicians to educate about this risk factors.